Biatrial mixoma. Report of a case - Conde-Vela, César (2007)
We report a case of biatrial mixoma in a 16 year-old patient who complained of exertional dyspnea. Transesophageal echocardiogram showed a large biatrial, mobile mass. Surgical resection and subsequent histopathologic examination identified a biatrial myxoma. Patient’s postoperative evolution and recovery was satisfactory.